India and Germany: Global Partnership in 21st century - Khashimwo, Pamreihor (International Journal of Scientific Research and Management (IJSRM), 2015)
Nehru and Adenauer established diplomatic relations in 1951. After an auspicious beginning in theearlyperiod, relationship between India and Germany were caught in the stagnations of benign neglect from 1960sto1980s. Following the India’s economic reforms and subsequent economic growth attracted the interest ofGermany.India is Germany’s most important scientific and technological cooperation partner in South Asia and bothcountrieshave entered a strategic partnership in education, science and research which offers the basis for diverseforms ofcooperation. How will these two central powers in the world interact with each other in 21st century? Thepaperfocuses on to promote an extensive understanding of the Indo-German perspectives for mutual relations as wellas theforeign policy outlooks in a changing international milieu. The main issues will be to widen the existing edificetocover traditional and non-traditional security issues. Also, it is essential and time for both India and Germany tomovethe relations beyond the purchase of BMW and Mercedes car.